Richness and composition of gall-inducing arthropods at Coiba National Park, Panama - Luis Nieves Aldrey, José (2008)
Interest in studying galls and their arthropods inducers has been growing rapidly in the last two decades. However, the Neotropical region is probably the least studied region for gall-inducing arthropods. A study of the richness and composition of gall-inducing arthropods was carried out at Coiba National Park in the Republic of Panama. Field data come from samples obtained between August 1997 and September 1999, with three (two-week long) more intensive samplings. Seventeen sites, representing the main land habitats of Coiba National Park were surveyed. 4942 galls of 50 insect and 9 mite species inducing galls on 50 vascular plants from 30 botanical families were colleted. 62.7% of the galls were induced by gall midges (Diptera, Cecidomyiidae), 15.3% by mites, Eriophyidae, 8.5% by Homoptera, Psyllidae, 6.8% by Coccidae and 5.1% by Phlaeothripidae (Tysanoptera). The host plant families with the most galls were Myrtaceae with seven, Bignoniaceae with five and Euphorbiaceae, Fabaceae and Melastomataceae with four. Leaf galls accounted for about 93% of collected galls. Most leaf galls were pit/blister galls followed by covering and pouch galls. Gall richness per collecting site was between 1 and 19 species. Coiba's gall diversity is discussed in relation to data available from other tropical sites from continental Panama and the Neotropical region. Our results support the idea that it may be premature to conclude that species richness of gall inducers declines near the equator.